Clinical outcome of elastic seton in comparison to non elastic seton in the management of adult patients with complex anal fistula -a randomized controlled trial - Tasnim, Tamanna; Hossain, Md Shahadat; Taher, Md Abu; Fatema, Bilkis; Mostofa, Golam; Alam, Ariful (Journal of Surgical Sciences, 2025)
Background: Complex fistula-in-ano is a therapeutic challenge for both the surgeon and the patient. Surgery is associated with significant morbidity despite of recent advances in treatment modalities. The aim of this study was to evaluate the outcome of elastic seton for the management of complex anal fistula. Methods: This prospective randomized controlled trial was done in clinically diagnosed patients of complex anal fistula who underwent operation by cutting seton placement in the colorectal surgery unit, department of surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from May, 2015 to April, 2016. Total 36(50%) patients treated by application of elastic seton (Experimental group) were included in group I and 36 (50%) patients treated by non-elastic seton (control group) were included in group II after randomization by lottery. Post-operative outcome variables within 6 months follow up after surgery were evaluated. Results: In this study, majority of the patients were found in between 30 to 50 years of age and in the both groups, number of male were higher. Mean healing time was 42.91±13.71 days in elastic seton group and 77.36±17.29 days in non-elastic seton group. Staged fistulotomy was required in 35(97.2%) cases of group-II whereas no cases of Group-I required staged fistulotomy. Mean duration of seton in place was 17.02±7.07 days in Group-I and 52.38±7.28 days in group-II. No significant difference of post-operative pain, incontinence and recurrence in both groups. Conclusion: This study showed that the elastic cutting seton may be a valid alternative for the treatment of complex anal fistula, eliminating the need for postoperative adjustment or staged procedure. Journal of Surgical Sciences (2021) Vol. 25 (1) : 36-41